Electrospun MXene/polyimide nanofiber composite separator for enhancing thermal stability and ion transport of lithium-ion batteries - Wu, Yitian; Wei, Wenhui; Feng, Tianxue; Li, Wenwen; Wang, Xiaoyu; Wu, Tao; Zhang, Xingshuang (Frontiers in Chemistry, 2025)
Safety of lithium-ion batteries (LIBs) has garnered significant attention. As an essential component of batteries, the separator plays a crucial role in separating the positive and negative electrodes, preventing short circuits, and allowing ion transport. Therefore, it is necessary to develop a high-performance separator that is both thermally stable and capable of rapid Li+ transport. Polyimide (PI) is a material with high thermal stability, but low electrolyte wettability and high interfacial resistance of PI restrict its application in high-performance LIBs batteries. MXene possesses excellent mechanical properties and good electrolyte affinity. PI/MXene nanofiber composite separator. Combines the high thermal stability of PI with the superior electrolyte wettability of MXene. It exhibits a high tensile strength of 19.6 MPa, low bulk resistance (2.5 Ω), and low interfacial resistance (174 Ω), as well as a low electrolyte contact angle of 29°, while retaining the high-temperature resistance and flame retardancy of PI. Batteries assembled with this composite separator demonstrated a specific capacity of 111.0 mAh g−1 and a capacity retention rate of 66% at 2C. In long-term cycling tests of LiFePO₄ half-cells at 1C, after 200 charge-discharge cycles, the PI/MXene battery showed a discharge specific capacity of 126.7 mAh g−1 and a capacity retention rate of 91%. Additionally, the battery operated normally at 120°C. The composite separator, by integrating the high thermal stability of PI with the excellent electrolyte wettability and conductivity of MXene, demonstrates significant advantages in enhancing battery safety and cycling performance. Through this composite structure can provide a more reliable and safe solution for high-performance LIBs.